ABSTRACT - Fazri Napril; Ahmad Mulyadi Sirodjul; Inpurwanto Wi (Fakultas Pertanian Universitas Tanjungpura, 2020)
The continuous catches of freshwater prawns in Batu Ampar Village done by fishermen are predicted to cause a decrease in the stock of freshwater prawns. This study aims to estimate the stock of freshwater prawns in this village. Research variables cover the frequency distribution of carapace length, the relationship between length and weight, growth rate, and mortality as well as the exploitation rate of freshwater prawns. The data were collected in October - December 2019 from collectors in Batu Ampar Village. The data were then analyzed using Ms. Excel Software and FISAT II (FAO-ICLARMStock Assessment TolII). The results showed the frequency distribution of carapace lengths in male and female prawns with sizes of 31-36 mm. Analysis of the relationship between the length and weight showed a negative allometric growth pattern with b-values of 1.98 for male prawns and 1.82 for female prawns. Male prawns have an asymptotic length of (L?) 91.5 mm, with a growth coefficient of 0.40 per year. Meanwhile, female prawns have values of (L?) 75 mm with a coefficient of 0.38 per year. The slow growth of female prawns was due to the allocation of energy needed to ripen the gonads until spawning. The exploitation rate (E) of the result of prawn catches in Batu Ampar Village showed a low utilization rate (under exploited).